Weddings in Korea and Ukraine - Hong, Sogu (Array, 2020)
Koreans and Ukrainians are two different nations in many aspects, such as geography, language, ethnicity, culture, and so on. It may seem difficult to find something in common between them. However, in terms of folk culture, especially wedding rituals, I would say that the two nations have many things in common. This study attempts to compare the traditional wedding rituals of the two nations which were performed among commoners between the 19th and the beginning of the 20th centuries. Through this study, we can understand that the basic structure of the wedding rituals of both cultures have much in common. Even though the ritual forms and contents are different from each other, both cultures use many similar objects and symbolic expressions for the wedding ceremony. This study also deals with how women’s work, romance and new aspirations of social class transformed the marriage tradition, and how rituals were influenced by the intervention of the governments’ authority in personal life.